About Clustering of Complex Syntactic Structures - HAKOBYAN, ANOUSH (Bulletin of Yerevan University H: Russian Philology, 2021)
The author considers complex linguistic structures having one and two levels, in which each component itself can be complicated binomial complex co-ordinative conjunctive, or disjunctive, or implicative sentences. Full specification of complex syntactic structures was made by functional and meaningful features, based on the various possibilities of co-ordination between the component parts of the functional connections. As result 27 classes have been identified. Utterances from the same cluster describe the same types of possible actual interconnections of the same species that are shown in two componentparts of complicated sentences.
Keywords: complex syntactic structures, binomial sentence, statement, clustering